Occupational exposure of firefighters to polycyclic aromatic hydrocarbons in non-fire work environments - Oliveira, M. (2018)
This work aims to characterize personal exposure of firefighters to polycyclic aromatic hydrocarbons (PAHs) in non-fire work environments (fire stations), and assesses the respective risks. Eighteen PAHs (16 considered by USEPA as priority pollutants, dibenzo[a,l] pyrene and benzo[j] fluoranthene) were monitored in breathing zones of workers at five Portuguese fire stations during a normal shift. The obtained levels of PAHs fulfilled all existent occupational exposure limits as well as air quality guidelines with total concentrations (Sigma PAHs) in range of 46.8-155 ng m(-3). Light compounds (2-3 rings) were the most predominant congeners (74-96% of Sigma PAHs) whereas PAHs with 5-6 rings accounted 3-9% of Sigma PAHs. Fuel and biomass combustions, vehicular traffic emissions, and use of lubricant oils were identified as the main sources of PAHs exposure at the studied fire corporations. Incremental lifetime cancer risks were below the recommend USEPA guideline of 10(-6) and thus negligible for all the studied subjects, but WHO health-based guideline level of 10(-5) was exceeded (9-44 times) at all fire corporations. These results thus show that even during non-fire situations firefighters are exposed to PAHs at levels that may promote some adverse health outcomes; therefore the respective occupational exposures to these compounds should be carefully controlled. (C) 2017